Analytical Study of Financial Planning trends with a focus on Public Expenditures in Iraqi Budgets for the period (2009-2020) - et. al, A. L. Mustafa Sameer Abdullah AL Samouak, (Turkish Journal of Computer and Mathematics Education (TURCOMAT), 2021)
In preparing the financial plans, the planners depend on the financial resources derived from the sale of oil owned by the country, to link these plans and the expenditures they contain with the financial resources obtained from selling crude oil. Therefore, these plans were not built on scientific methods or studies of the Iraqi economic reality and according to its needs. Therefore, the research will seek to study and analyze financial planning trends in Iraq, with a focus on public expenditure trends during the period (2009-2020). The research adopts a hypothesis that “public expenditure in the financial plans estimated in the Iraqi budgets did not follow sound and scientific methods and mechanisms according to the financial planning process, as well as being affected by the oil nature of the Iraqi economy,” relying on the deductive approach using the descriptive method. The research concluded that the financial planning in Iraq was based on improper planning mechanisms, and was not based on modern scientific methods to direct financial resources in the directions of achieving economic goals as desired by the philosophy of the economic and financial plans of the Iraqi government. Therefore, the research recommends the necessity of financial planning at the level of the Iraqi economy and at the level of its economic sectors and government agencies, based on financial and economic studies, and procedures that take the economic reality and its situation in which it passes into account according to the actual immediate and future needs, in order to improve the reality and economic conditions in Iraq. As well as paying attention to the process of reforming the Iraqi public budget preparation programs and adhering to their timing, and setting economic goals in a way that achieves development and prosperity for the country.